2015
DOI: 10.7448/ias.18.1.19467
|View full text |Cite
|
Sign up to set email alerts
|

PRINCE‐1: safety and efficacy of atazanavir powder and ritonavir liquid in HIV‐1‐infected antiretroviral‐naïve and ‐experienced infants and children aged ≥3 months to <6 years

Abstract: IntroductionPRINCE-1 is an ongoing prospective, international, multicentre, nonrandomized, two-stage clinical trial assessing safety and efficacy of once-daily atazanavir (ATV) powder boosted with ritonavir (RTV) liquid plus optimized dual nucleoside reverse-transcriptase inhibitor (NRTI) background therapy in antiretroviral (ARV)-naïve and -experienced children with HIV-1 infection aged ≥3 months to <6 years.MethodsChildren with HIV-1 infection without prior ATV exposure and with a screening HIV-1 RNA ≥1000 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…The PRINCE I and PRINCE II trials showed that ATV powder formulation in combination with RTV liquid in children 3 months to <11 years and weighing 5 to <35 kg dosed in weight bands reached the target drug exposure levels. 61,65,66 Results from the PRINCE I and II trials together with IMPAACT P1020 and the modeling study by Hong et al supported the FDA approval of ATV/r doses in children (see Table 3 , Supplemental Digital Content 2 , http://links.lww.com/TDM/A324).…”
Section: Methodsmentioning
confidence: 81%
“…The PRINCE I and PRINCE II trials showed that ATV powder formulation in combination with RTV liquid in children 3 months to <11 years and weighing 5 to <35 kg dosed in weight bands reached the target drug exposure levels. 61,65,66 Results from the PRINCE I and II trials together with IMPAACT P1020 and the modeling study by Hong et al supported the FDA approval of ATV/r doses in children (see Table 3 , Supplemental Digital Content 2 , http://links.lww.com/TDM/A324).…”
Section: Methodsmentioning
confidence: 81%
“…In addition, many of the newer ARVs are better tolerated and provide additional options for treatment should modifying ART as a result of intolerance become necessary. Most studies of ART-associated toxicity in children have reported only grade 3 or higher adverse events or are limited to short-term follow-up [22][23][24] and include children on ART but with elevated HIV RNA levels. It can be difficult to sort the medication effects from the effects of active viral replication, which itself can lead to elevations in liver enzyme levels [25], neutropenia, thrombocytopenia, and anemia [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 1.085 records identified, 901 titles and abstracts were screened after duplicates removed. Overall, 23 full papers were assessed for eligibility, of which five were included in the narrative synthesis ( Figure 1 ) ( 22 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…Those five studies contributed data for 975 children and adolescents, of whom 544 (56%) received atazanavir. Three were observational cohort studies ( 22 , 23 , 25 ) (two retrospective and one prospective comparative, based on a phase 3b clinical trial) and two were prospective non-randomized clinical trials ( 24 , 26 ). The single comparative cohort study ( 23 ) compared atazanavir-based with darunavir-based regimens, and was conducted in Europe and Thailand between 2011 and 2014.…”
Section: Resultsmentioning
confidence: 99%